Multi-purpose magnetic coupling agent based on graphene
By using graphene materials and vacuum planetary dispersion processes, the existing magnetic coupling agents have been solved in terms of temperature stability, corrosion resistance and high-frequency mechanical oscillation resistance, and the multi-purpose application and high-efficiency performance of magnetic coupling agents are achieved.
Patent Information
- Application Number
- CN202411813877.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-25
AI Technical Summary
The existing magnetic coupling agents have shortcomings in temperature stability, corrosion resistance and high-frequency mechanical oscillation resistance, and cannot be removed and used again, limiting their application convenience.
High-permeable paste is developed using graphene materials, combined with vacuum planetary dispersion technology, and magnetic coupling agents with non-Newtonian fluid characteristics are prepared to enhance their temperature stability, friction performance and magnetic permeability.
It has achieved the improvement of the temperature stability, chemical stability and friction performance of magnetic coupling agent, solved the problem that the magnetic gel cannot be reused after solidification, and is suitable for frequent opening and closing of magnetic core coupling applications.
Smart Images

Figure CN119889858A_ABST
Abstract
Description
Technical Field
[0001] The present invention particularly relates to a multi-purpose magnetic coupling agent based on graphene. Background Art
[0002] In order to improve the contact quality of the magnetic circuit, the mainstream measures often taken by the industry are mechanical grinding and polishing at the connection of the magnetic circuit, adding magnetic gaskets, using solid magnetic adhesives, etc. Although grinding and polishing have certain effects, the operation is complicated, the assembly process is high, and the contact surface is not protected. For some magnetic cores made of ferromagnetic materials, there is still the problem of increased magnetic resistance caused by environmental aging. The use of magnetic gaskets can also reduce the magnetic resistance, but it also cannot provide good chemical protection for the contact surface of the magnetic circuit. Magnetic adhesives are often used in static magnetic circuits such as mutual inductors and transformers. Their tight combination provides effective contact surface protection, but once it solidifies, it cannot be removed and used again, and its convenience is weak. In recent years, there are some new types of magnetic coupling agents that can solve the problem of high magnetic resistance of the contact surface of the magnetic circuit that needs to be frequently opened and closed, such as mutual inductors and magnetic field sensors, to a certain extent. However, due to the paste characteristics, these magnetic coupling agents have the disadvantages of poor temperature stability, easy flow, and poor corrosion resistance. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a multi-purpose magnetic coupling agent based on graphene.
[0004] The technical solution adopted by the present invention is as follows: a multi-purpose magnetic coupling agent based on graphene, the magnetic coupling agent comprising base oil, thickener, soft magnetic ferrite, dispersant, graphene, and wear-resistant agent; The preparation method comprises the following steps: Step 1: adding graphene and dispersant to base oil, dispersing, and obtaining base liquid; Step 2: Combine the dispersant and the soft ferrite to obtain a premixed filler; Step 3: Add the premixed filler prepared in step 2 into the base liquid, stir until the filler and the base liquid are mixed together, then add the thickener and the anti-wear agent, the mixture becomes a semi-solid state, and stir thoroughly until the mixture becomes soft to obtain a preliminary mixture; Step 4: Place the preliminary mixture in a mixer and disperse and mix it through a vacuum planetary dispersion process, during which thickener and anti-wear agent are added.
[0005] The invention utilizes the characteristics of high physical and chemical stability, high Young's modulus, and high specific surface area of graphene materials to develop a high-permeability magnetic paste, and makes it have the advantages of strong temperature stability, appropriate hardness, strong friction performance, and high magnetic permeability characteristics, which can realize multi-purpose application functions. This feature effectively solves the problems of reduced efficiency and decreased system stability caused by poor magnetic circuit contact, thereby improving overall performance and reliability. In addition, a vacuum planetary dispersion method is used to vacuum disperse flaky graphene powder into the interior of the magnetic coupling agent paste to prepare a magnetic coupling agent paste with non-Newtonian fluid properties. While having higher fluidity, it improves its tolerance to high-frequency mechanical shocks, and at the same time improves the temperature stability, chemical stability, and friction performance of the paste.
[0006] The base oil needs to be high temperature resistant and corrosion resistant. Since phenyl silicone oil has strong high temperature resistance and good corrosion resistance, phenylmethyl silicone oil is preferably used as the base oil of the magnetic coupling agent.
[0007] In addition to phenylmethyl silicone oil, the following raw materials can also be considered as base oils: 1. Synthetic ester base oil: This type of base oil usually has excellent high temperature resistance and lubrication performance, and can provide good corrosion protection. However, its hydrolysis resistance is poor. Synthetic ester base oil may be easily hydrolyzed under certain conditions, resulting in performance degradation.
[0008] 2. Polyalphaolefin (PAO) base oil: PAO base oil has excellent thermal and chemical stability and is suitable for high temperature and high load application environments. However, in some cases, PAO base oil may not be able to completely dissolve certain additives, which may affect the performance of the magnetic coupling agent.
[0009] 3. Mineral oil: Although mineral oil's high temperature resistance and corrosion protection may be slightly inferior to synthetic oil, it may be more cost-effective in certain specific applications.
[0010] Thickener refers to a substance that can increase the viscosity of a liquid and turn it into a semi-solid or solid state. In the present invention, the thickener needs to have good heat resistance and chemical stability, so an inorganic thickener is preferably used, and fumed silica is most preferably used, which has good thickening ability, high temperature stability and wear resistance.
[0011] In addition to fumed silica, the following materials can also be considered as thickeners: 1. Bentonite: Bentonite has good water absorption and swelling properties and can be used to increase the viscosity of liquids. However, the dispersibility and stability of bentonite in solvents may be affected, resulting in a decrease in the thickening effect. 2. Diatomaceous earth: Diatomaceous earth has a high specific surface area and adsorption capacity, and can be used as a thickener to increase the consistency of the liquid. However, diatomaceous earth may generate dust during processing, which may cause potential harm to the environment and the health of operators.
[0012] 3. Graphite: Graphite has lubricity and high temperature resistance. It can increase the viscosity of the liquid to a certain extent while providing good lubrication effect.
[0013] Wear-resistant agents refer to additives that can improve the wear resistance of materials. Polytetrafluoroethylene has an extremely low friction coefficient and can effectively improve wear resistance.
[0014] In addition to PTFE, the following materials can also be considered as wear-resistant agents: 1. Molybdenum disulfide (MoS2): Molybdenum disulfide has an extremely low friction coefficient and excellent lubrication properties, and can be used as an anti-wear agent to improve the wear resistance of materials. However, the thermal conductivity of molybdenum disulfide is relatively poor, which may affect the heat dissipation performance of the magnetic coupling agent in a high temperature environment.
[0015] 2. Graphite powder: Graphite powder also has lubricity and wear resistance, and can be used to improve the wear resistance of magnetic coupling agents. However, graphite powder is easily oxidized when exposed to air for a long time, resulting in a decrease in its performance.
[0016] 3. Silicon carbide (SiC): Silicon carbide is a material with extremely high hardness and good wear resistance and anti-wear properties, and can be used as a wear-resistant additive. However, rapid temperature changes may cause thermal stress inside the material, thus affecting its durability and life.
[0017] Soft ferrites are mainly composed of iron oxide and other metal oxides (such as nickel oxide, zinc oxide, etc.).
[0018] The cone penetration of the magnetic coupling agent is 70-90. The cone penetration mainly reflects the hardness of the magnetic coupling agent and is one of the basic physical and chemical performance indicators of the paste. If the cone penetration is too large, the overall viscosity is low. If the cone penetration is too small, the magnetic coupling agent is too hard, and it is difficult to apply evenly during use. It is easy to form bubbles and dry up, resulting in incomplete contact between the contact area, which greatly increases the contact magnetic resistance and destroys the quality of the magnetic circuit connection. The cone penetration of the magnetic coupling agent of the present invention is controlled within the range of 70-90 to meet the actual engineering needs and can avoid problems such as being too hard or too soft.
[0019] Preferably, in step 1, the base oil is allowed to stand to eliminate surface bubbles before use.
[0020] Preferably, in step 2, the soft ferrite is dried in advance before use, and added to a high-speed disperser and stirred to be evenly dispersed.
[0021] Preferably, in step 1, the graphene is dried in advance before use.
[0022] Preferably, the thickener and the anti-wear agent are pre-mixed, divided into two halves, and added in step three and step four respectively.
[0023] Preferably, in step 4, the preliminary mixture is placed in a blender and the blending is set to three stages: in the first stage, conventional high-speed dispersion is performed at atmospheric pressure for 80 seconds at a rotation speed of 1200 r / min to remove large bubbles in the sample; in the second stage, vacuum high-speed dispersion is performed for 120 seconds at a rotation speed of 1800 r / min to completely evacuate the bubbles in the sample; in the third stage, atmospheric pressure is released and high-speed dispersion is performed for 60 seconds at a rotation speed of 1500 r / min; the rotation ratio of the three stages is 1:0.5.
[0024] The magnetic coupling agent provided by the present invention is a high magnetic permeability paste, which has the advantages of strong temperature stability, appropriate hardness, strong friction performance, high magnetic permeability characteristics, etc., and has extremely high vibration tolerance, temperature stability and chemical stability while having deformation ability. It solves the problem that the magnetic adhesive cannot be used again once it is solidified, and also avoids the problems of poor vibration tolerance and easy flow at high temperature of existing magnetic pastes on the market. It has the ability of high magnetic permeability to solve the efficiency reduction and stability reduction caused by poor magnetic circuit contact, and is suitable for application scenarios of magnetic core coupling with frequent opening and closing.
[0025] The magnetic coupling agent prepared by the method of the present invention has a uniform distribution of fillers and is not prone to precipitation.
[0026] At the same time, the magnetic coupling agent of the present invention has extremely high temperature stability. It is tested by dropping point. Dropping point (DP) is a property of a material. The sample is heated until it changes from solid to liquid. Dropping point refers to the temperature when the first drop of molten material drips from a standard cup with a specified orifice under controlled test conditions in a furnace. In the dropping point test, the dropping point of the graphene magnetic coupling agent of this patent can reach up to 330°C, far exceeding other types. It shows that the performance of the graphene magnetic coupling agent is more stable in a high temperature environment.
[0027] In the friction surface performance test, the graphene magnetic coupling agent of this patent has excellent friction performance and good wear resistance.
[0028] Comprehensive analysis shows that graphene magnetic coupling agent is superior to other types of magnetic coupling agents in terms of dropping point, cone penetration and friction surface performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.
[0030] Figure 1 The wear scar morphology of steel balls with magnetic coupling agents of different graphene contents, where (a) is 3% graphene content, (b) is 4% graphene content, (c) is 5% graphene content, (d) is 6% graphene content, and (e) is 7% graphene content; Figure 2 The morphology of graphene magnetic coupling agents with different concentrations, where (a) is 3% graphene content, (b) is 4% graphene content, (c) is 5% graphene content, (d) is 6% graphene content, and (e) is 7% graphene content; Figure 3 Surface energy spectra of wear scars of graphene magnetic coupling agent, where (a) is 3% graphene content, (b) is 4% graphene content, (c) is 5% graphene content, (d) is 6% graphene content, and (e) is 7% graphene content; Figure 4 This is the hysteresis curve of the magnetic coupling agent. DETAILED DESCRIPTION
[0031] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.
[0032] Embodiment 1: The main raw materials involved in this embodiment are shown in Table 1.
[0033] The amounts of the main raw materials involved in this embodiment are shown in Table 2.
[0034] The preparation steps of this embodiment are as follows: (1) Selection of base oil: Weigh a certain amount of phenyl silicone oil using an electronic balance and place it in a constant temperature environment at room temperature for 3 minutes to eliminate surface bubbles.
[0035] (2) Take a quantity of polytetrafluoroethylene and fumed silica and mix them evenly in advance.
[0036] (3) Pretreatment before proportioning: Place the soft ferrite and graphene in an electric constant temperature blast drying oven (80°) and dry them in advance for 30 minutes to remove moisture from the powder. Add the soft ferrite to a high-speed disperser (1500r / min) and stir mechanically for 10 minutes to disperse it evenly. Add a suitable proportion of graphene and part of the sodium dodecyl sulfate dispersant to the base oil and stir in a high-speed disperser (2200r / min), and perform ultrasonic dispersion for 30 minutes to break up the graphene agglomeration and prepare a base liquid. (The conductive filler is the soft ferrite and graphene; the soft ferrite can be added together with the premixed filler; the order is: 1. Graphene 2. Dispersant 3. Filler mixed with dispersant and soft ferrite 3. Thickener 4. Anti-wear agent) The dispersant and soft ferrite are combined to obtain a premixed filler. (4) mixing the remaining portion of the sodium dodecyl sulfate dispersant and the soft ferrite to obtain a premixed filler; (5) Preliminary mixing of samples: Add the premixed filler prepared in advance to the base liquid at a uniform speed, stir mechanically for 10 minutes, wait until the premixed filler and phenyl silicone oil are mixed together, add half of the thickener silica and the wear-resistant agent polytetrafluoroethylene. At this time, the solution will become a semi-solid state. Stir thoroughly for 10 minutes, wait until the mixed material begins to soften, and let it stand for 3 minutes.
[0037] (6) The preliminarily mixed sample is placed in a Smaida mixer (set up a three-stage program. The first stage is conventional high-speed dispersion under atmospheric pressure for 80 seconds, with a rotation speed of 1200 r / min, to remove large bubbles in the sample; the second stage is vacuum high-speed dispersion for 120 seconds, with a rotation speed of 1800 r / min, to completely vacuum the bubbles in the sample; the third stage is atmospheric pressure release and high-speed dispersion for 60 seconds, with a rotation speed of 1500 r / min; the three-stage program has a rotation ratio of 1:0.5). During this period, the remaining silicon dioxide and polytetrafluoroethylene are gradually added to the sample in two batches, and the vacuum stirring is completed. The sample is left to cool naturally to room temperature to prepare a magnetic coupling agent.
[0038] (7) Conduct friction surface analysis and cone penetration tests on the product to select the most suitable formula.
[0039] Test Example 1: The magnetic coupling agent prepared in Example 1 was evenly coated on a glass slide with a scraper, with a coating thickness of 1 mm to 2 mm. After observation under light, the five magnetic coupling agents with different graphene contents prepared in Example 1 were evenly fine and smooth, without obvious granularity, and in good condition. It can be seen that the magnetic coupling agent prepared by the method of the present invention has evenly distributed fillers and is not easy to precipitate.
[0040] Test Example 2: The cone penetration of the graphene magnetic coupling agent of the present invention tends to decrease with the increase of graphene content. The cone penetrations of the five magnetic coupling agents with different graphene contents prepared in Example 1 are all within the range of 70-90, which meets the actual engineering needs and can avoid problems such as being too hard or too soft.
[0041] Test Example 3: The dropping point is tested. The dropping point (DP) is a property of a material. The sample is heated until it changes from a solid to a liquid state. The dropping point refers to the temperature at which the first drop of molten material drips from a standard cup with a specified orifice under controlled test conditions in a furnace. In the dropping point test, the dropping points of the five magnetic coupling agents with different graphene contents prepared in Example 1 are significantly higher than other types of magnetic coupling agents in the prior art, up to 330°C, indicating that the performance of the graphene magnetic coupling agent is more stable in a high temperature environment.
[0042] Test example 4: The five magnetic coupling agents with different graphene contents prepared in Example 1 were taken as research objects. The friction coefficients and wear scar diameters were studied through relevant experiments. The wear scar diameter of the steel ball was observed at a magnification of 100 times under a high-definition CCD measuring instrument. The friction surface of the worn coupling agent was analyzed to study its friction reduction and anti-wear mechanism.
[0043] Figure 1 As shown in the figure, under the conditions of load 147N and 800r\min, the friction surface of the steel ball was observed by magnifying it 100 times with a high-definition CCD measuring instrument, and the morphology of the friction surface of the steel ball under five kinds of magnetic coupling agents was given. It can be seen that the wear marks on the friction surface under the coupling agent with 5wt% graphene content are relatively smooth, and only some shallow furrows appear on the surface. A large number of furrows and pits appeared on the wear surface under the other four kinds of magnetic coupling agents with graphene content. Figure 1 (a) Clear and deep grooves appeared on the friction surface of the steel ball under the coupling agent with 3wt% graphene content. This is due to the combined cutting action of the positive pressure and lateral rotation force of the steel ball matrix in the vertical direction, and the friction surface showed serious wear marks. Therefore, the friction coefficient and wear amount of the coupling agent with 3wt% graphene content are larger. As the graphene content increases, Figure 1 As shown in (b)-(e), the grooves on the friction surface of the steel ball begin to become shallower.
[0044] It can be found that with the increase of graphene content in the coupling agent, the wear caused by abrasive particles is effectively suppressed, resulting in shallow scratches on the worn surface. This is mainly because the friction surfaces in contact with each other are uneven, and the nano-sized graphene particles are filled into the pits of the friction contact surface with the flow of the coupling agent, which reduces the roughness of the friction surface to a certain extent, making the surface relatively smoother, thereby reducing the friction coefficient. In addition, due to the thin layered structure of graphene, it is easy to dissociate along the interlayer in the friction test and deposit on the friction surface to form a protective film, thereby protecting the friction surface. When the content of graphene in the magnetic coupling agent is low, it is not enough to fill the pits on the friction surface. When the content is high, graphene is prone to agglomeration, so that the uneven parts of the friction surface cannot be fully filled, which destroys the continuity of the graphene distribution in the magnetic coupling agent oil film, and reduces the friction reduction and anti-wear effect. Adding an appropriate amount of graphene magnetic coupling agent can greatly improve the friction and wear contact surface of the steel ball. Therefore, by observing the friction surface morphology, it can be found that the wear resistance is 5wt%>6wt%>7wt%>4wt%>3wt%. When adding a magnetic coupling agent with a graphene content of 5wt%, the friction reduction and anti-wear effect is the best.
[0045] In order to further study the friction and wear mechanism of graphene magnetic coupling agents, scanning electron microscopy was used to characterize the morphology and structure of five magnetic coupling agents with different graphene contents after the four-ball friction test at a magnification of 2000 times. The internal structure of the graphene magnetic coupling agent can be clearly observed. Figure 2 As shown in the figure, the bright part is the metal material dropped by the friction between the conductive metal powder particles in the filler and the steel ball, the dark area is the silicone oil matrix, and the dark area is the graphene particles. Figure 2 The distribution of conductive metal particles and graphene in (a)-(e) shows that the metal particles are largely agglomerated, and the graphene particles around the conductive metal particles are also agglomerated on a large scale. Because the coupling agent is a paste-like substance, its fluidity is far inferior to that of a liquid. After high-speed rotation and shearing in a four-ball friction tester, agglomeration is normal. Figure 2 (c) The internal dispersion of the 5wt% graphene magnetic coupling agent is good, and it can fill the deep scratches on the surface when the steel ball rubs against the contact surface. Therefore, it has good friction reduction and anti-wear properties.
[0046] Under the conditions of 147N and 800r\min, the main elements and contents of the coupling agent on the wear scar surface were analyzed using an energy dispersive spectrometer (EDS), as shown in Table 3.
[0047] Table 3 Element contents of five graphene magnetic coupling agents Figure 3The EDS spectra of the scratches on the friction surface of the steel ball made by magnetic coupling agents with five different graphene contents are shown in Figure 2. Figure 3 a) It can be seen that there are mainly four elements C, O, Si and Fe on the scratch surface. Si is an element in the silicone oil matrix, and Fe is a conductive filler in the coupling agent. The content of C element in the five coupling agents with different graphene contents in the wear marks is significantly higher. Obviously, the C element in the wear marks comes from the graphene in the magnetic coupling agent, and its wear marks form a protective film containing graphene on the friction surface. It can be seen from the table that the wear mark surface contains a certain amount of oxygen element. The large amount of heat generated during the friction process undergoes an oxidation reaction at high temperature, forming a dense oxide film on the scratch surface, which protects the scratch. Comparison Figure 3 ae) It can be seen that when the graphene content in the coupling agent is 5wt%, the content of C element and oxygen element is the highest, which shows a better protective effect on the scratched surface, so the friction reduction and anti-wear effect shown in the friction process is the best.
[0048] When the external magnetic field strength begins to increase, the magnetization intensity of the coupling agent can increase rapidly, but when the magnetic field strength increases to a certain extent, the growth rate of the magnetization intensity of the coupling agent particles gradually slows down, so that the magnetization intensity value gradually tends to the saturation magnetization intensity: when the external magnetic field strength decreases, the magnetization intensity of the coupling agent particles also decreases. When the external magnetic field strength gradually decreases to zero, the magnetization intensity also decreases, but it does not completely return to zero, so it has a certain remanence and coercive force. The hysteresis curve of the coupling agent is shown in Figure 4 From the figure, we can see that its saturation magnetization reaches 69.31emu / g, but the coercive force is very small and close to zero. Therefore, graphene-based magnetic coupling agents have broader application prospects in improving the magnetic conductivity of magnetic circuits.
[0049] The magnetic permeability test was conducted on the magnetic circuit without magnetic coupling agent and the magnetic circuit with magnetic coupling agent, and the test results are shown in Table 4. As can be seen from Table 4, when the magnetic coupling agent is used, the relative magnetic permeability is linearly distributed with the increase of the weight of the magnetic coupling agent, and is in a proportional function relationship; when the magnetic coupling agent exceeds 8g, the enhancement speed and amplitude are much slower, but there is still a high relative magnetic permeability. It can be seen that the magnetic coupling agent has a high magnetic conductivity.
[0050] Table 4 Comparison of relative magnetic permeability The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.
Claims
1. A multi-purpose magnetic coupling agent based on graphene, characterized in that: The magnetic coupling agent comprises: Base oil 27-31 parts by mass; Thickener 4-6 parts by mass; Soft ferrite 53-57 parts by mass; 3-5 parts by mass of dispersant; Graphene 3-7 parts by mass; 1.5-2.5 parts by weight of anti-wear agent; The preparation method comprises the following steps: Step 1: adding graphene and dispersant to base oil, dispersing, and obtaining base liquid; Step 2: Mixing the dispersant and the soft ferrite to obtain a premixed filler; Step 3: Add the premixed filler prepared in step 2 into the base liquid, stir until the filler and the base liquid are mixed together, then add the thickener and the anti-wear agent, the mixture becomes a semi-solid state, and stir thoroughly until the mixture becomes soft to obtain a preliminary mixture; Step 4: Place the preliminary mixture in a mixer and disperse and mix it through a vacuum planetary dispersion process, during which thickener and anti-wear agent are added.
2. The multi-purpose magnetic coupling agent of graphene according to claim 1, characterized in that: The base oil is benzyl silicone oil.
3. The multi-purpose magnetic coupling agent of graphene according to claim 1, characterized in that: The thickener is fumed silica, and the wear-resistant agent is polytetrafluoroethylene.
4. The multi-purpose magnetic coupling agent of graphene according to claim 1, characterized in that: The cone penetration of the magnetic coupling agent is 70-90.
5. The multi-purpose magnetic coupling agent based on graphene according to claim 1, characterized in that: In step 1, the base oil is allowed to stand to eliminate surface bubbles before use.
6. The multi-purpose magnetic coupling agent based on graphene according to claim 1, characterized in that: In step 2, the soft ferrite is dried in advance before use, and added into a high-speed disperser and stirred to be evenly dispersed.
7. The multi-purpose magnetic coupling agent based on graphene according to claim 1, characterized in that: In step 1, the graphene is dried in advance before use.
8. The multi-purpose magnetic coupling agent based on graphene according to claim 1, characterized in that: The thickener and anti-wear agent are pre-mixed, divided into two halves, and added in step three and step four respectively.
9. The multi-purpose magnetic coupling agent based on graphene according to claim 1, characterized in that: In step 4, the preliminary mixture is placed in a blender and three stirring programs are set. In the first program, conventional high-speed dispersion is performed for 80 seconds at atmospheric pressure and a rotation speed of 1200 r / min to remove large bubbles in the sample; in the second program, vacuum high-speed dispersion is performed for 120 seconds at a rotation speed of 1800 r / min to completely vacuum the bubbles in the sample; in the third program, atmospheric pressure is released and high-speed dispersion is performed for 60 seconds at a rotation speed of 1500 r / min; the rotation ratio of the three programs is 1:0.5.
Citation Information
Cited By
Current sensor performance improvement method based on magnetic coupling agent
CN119902143A
A method for improving performance of a current sensor based on a magnetic coupling agent
CN119902143B